Research on cultivating paths of English writing ability of high school students based on peer feedback from the correction network - Bo, Zhang; Razali, Abu Bakar; Ismail, Lilliati (Edelweiss Applied Science and Technology, 2025)
Most senior high school students face many difficulties in English writing, such as having nothing to say, being unorganized, using a single sentence pattern, and making frequent grammatical errors, which not only affect the quality of their writing but also increase their fear and powerlessness regarding writing. The purpose of this study is to explore the effectiveness of peer feedback on senior high school students’ English writing ability. The study adopts a combination of quantitative and qualitative methods and takes two parallel English classes in an urban public high school as the research subjects. Through a semester of experimental teaching, it conducts a comparative analysis of the changes in students’ English writing anxiety levels and writing performance in the experimental class (with peer feedback from the correction network) and the control class (with traditional teacher feedback). The results show that the level of English writing anxiety among the students in the experimental class significantly decreased, and their writing performance significantly improved, while the changes in these two aspects for the students in the control class were not significant. The qualitative analysis further reveals the positive effect of peer feedback on improving students’ writing ability and reducing their writing anxiety. The results of the study have implications for the teaching of English writing in senior high schools and suggest that teachers should attach importance to sentence practice, strengthen writing feedback, and optimize error correction methods in daily teaching to improve students’ English writing ability.